a^2+b)(b^2+a)
L.H.S=a^2b^2+a^3+b^3+ab
=4-1-8+2=-3
R.H.S=(a^2+b)(b^2+a)
=(1-2)(4-1)
=-3
2006-11-18 01:36:16
·
answer #1
·
answered by Chucky 2
·
0⤊
0⤋
(a^2 + b)*(b^2+a)=
a²b²+a³+b³+ab=
for a= -1,b= -2:
(-1)²(-2)²+(-1)³+(-2)³+(-1)(-2)
(1*4)+(-1)+(-8)+2=
4-1-8+2=
= -3 <<<<<<<<<<<<<<<<<<<<<<
proof:
(-1²-2)(-2²-1)=
(1-2)(4-1)=
-1*3=-3
₢
2006-11-18 07:13:41
·
answer #2
·
answered by Luiz S 7
·
0⤊
0⤋
Simply arithmetics, no binomials needed:
= (-1*-1+(-2))(-2*-2+(-1)) = (1-2)(4-1) = -1(3)= -3
2006-11-18 06:27:35
·
answer #3
·
answered by hb9tza/qrp 1
·
0⤊
0⤋
Q. (a^2+b)(b^2+a)
Ans.
(a^2)(b^2)+a^3+b^3+a*b
put a=-1 and b=-2
((-1)^2)((-2)^2)+(-1)^3+(-2)^3+(-1)(-2)
=> 1*4+(-1)+(-8)+2
=>the answer is -3
2006-11-18 06:31:58
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
a^2.b^2+a^3+b^3+ab
(ab)^2+a^3+b^3+ab
(-1.-2)^2+(-1)+(-8)+2
4-1-8+2
3-6
-3 (solved)
2006-11-18 06:14:25
·
answer #5
·
answered by fii 3
·
0⤊
0⤋
(a² + b)(b² + a)
[(- 1)² +( - 2)][(- 2)² + (-1)]
[1 - 2][4 - 1]
[-1][3]
- 3
The answer is - 3
- - - - - - - - - - -s-
2006-11-18 10:49:45
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
(a^2+b)(b^2+a)
=a^2b^2+a^3+b^3+ab
=4-1-8+2=-3
(a^2+b)(b^2+a)
=(1-2)(4-1)
=-3
2006-11-18 06:09:25
·
answer #7
·
answered by raj 7
·
0⤊
0⤋
11 was a racehorse 22was12 1111race22112
2006-11-18 06:13:51
·
answer #8
·
answered by graham b 1
·
0⤊
1⤋
ask ur maths teacher dear not here
2006-11-18 06:07:55
·
answer #9
·
answered by rick hei 2
·
0⤊
1⤋
*yawn*
maths is boring
2006-11-18 07:25:06
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋